Mitochondria and Their Role in Cardiovascular Disease - Marín-García, José. (Springer US : Imprint: Springer, 2013)
Over the past two decades, due to dramatic advances in molecular and cell biology, biochemistry, and genetics, our view on mitochondria as a relatively static cellular powerhouse has changed radically. We now know that these organelles play a critical role in the normal and in the damaged heart. Written by Dr. José Marín-García, Director of the Molecular Cardiology and Neuromuscular Institute, Mitochondria and Their Role in Cardiovascular Disease brings readers up- to-date on the many significant advances in the field of mitochondrial cardiovascular medicine.  The book begins with a general introduction to mitochondria, followed by laboratory methods to study the structure and function of the organelle, regulation of replication and biogenesis, and the mechanisms and functional consequences of mitophagia and mitochondrial dynamics. Subsequent chapters deal with mitochondrial oxidative stress and the role that the organelle plays in cell signaling and cell death. Discussions will be undertaken on the biochemistry of mitochondrial cell signaling, including the nature of the proteins engaged in these processes, many of them only recently discovered. Later chapters examine the role of mitochondria and mitochondrial abnormalities in cardiovascular diseases, including their diagnosis, therapeutic options currently available, animal models of mitochondrial disease, and new frontiers in mitochondria cardiovascular medicine, including areas of research that are relatively new or developing, such as proteomics, next generation sequencing, and systems biology.